Evaluation of Soil Fertility and Maize Crop Nutrient Status in Himalayan Region Poonch, Azad Jammu and Kashmir: Maize crop Nutrient status in Poonch Azad Kashmir - Khaliq, Abdul; Shaheen, Aqila; Ishaq, Summra; Zafar, Mohsin; M. Tahir, Majid; Zahoor, Tahir; Sarwar, Sair (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The judgment of the fertility status of agricultural soils is very substantial to determine crop sustainability and judicious nutrient management. A field survey of dominant maize growing areas of District Poonch, Azad Jammu, and Kashmir was undertaken in July-August, 2017. The twelve dominant maize growing sites, namely Char, Chak, Dothan, Banjusa, Chamber, Hajira Kelot, Kakuta, Mandhole, Madarpur, Tatrinote, Chattra Abbaspur, and Dawarandi were selected for the collection of soil and associated maize plant samples. A total of 24 composite soil samples (each representative of three individual samples) was separately collected from 0-15 and 15-30 cm depths and were analyzed for physicochemical characteristics, i.e. soil texture, pH, organic matter, soil nitrogen, available P, exchangeable K and micronutrients (Cu, Fe, Mn, and Zn). The maize ear leaves samples were also analyzed for N, P, K, and micronutrients (Cu, Fe, Mn, and Zn). To evaluate the adequacy levels of nutrients for maize growth the critical nutrient levels were used. Soils in the sampled sites were weakly acidic to neutral (pH 6.66-7.29) and had low to medium soil organic matter content (0.57-1.12%). The percent of sites with low nutrient contents were 66.7% for P and K, 8.3% for Cu,and 66.7% for Zn. The 100% sampled sites had plant N, P, and Cu deficiency while percent deficiency for plant K, Mn, and Zn was 1, 50, and 25, respectively. Soil pH had negative and organic matter had a positive significant correlation with all analyzed soil and plant nutrients. These results suggest that having integrated nutrient management strategies can enhance soil fertility and productivity in the study area.